Research priorities for conservation and natural resource management in Oceania's small‐island developing states. Issue 1 (5th September 2017) - Weeks, R.; Adams, V. M.
Abstract: For conservation science to effectively inform management, research must focus on creating the scientific knowledge required to solve conservation problems. We identified research questions that, if answered, would increase the effectiveness of conservation and natural resource management practice and policy in Oceania's small‐island developing states. We asked conservation professionals from academia, governmental, and nongovernmental organizations across the region to propose such questions and then identify which were of high priority in an online survey. We compared the high‐priority questions with research questions identified globally and for other regions. Of 270 questions proposed by respondents, 38 were considered high priority, including: What are the highest priority areas for conservation in the face of increasing resource demand and climate change? How should marine protected areas be networked to account for connectivity and climate change? What are the most effective fisheries management policies that contribute to sustainable coral reef fisheries? High‐priority questions related to the particular challenges of undertaking conservation on small‐island developing states and the need for a research agenda that is responsive to the sociocultural context of Oceania. Research priorities for Oceania relative to elsewhere were broadly similar but differed in specific issues relevant to particular conservation contexts. These differences emphasize the importance of involving local practitioners in the identification of research priorities. Priorities were reasonably well aligned among sectoral groups. Only a few questions were widely considered answered, which may indicate a smaller‐than‐expected knowledge‐action gap. We believe these questions can be used to strengthen research collaborations between scientists and practitioners working to further conservation and natural resource management in this region.